2015
DOI: 10.1021/acs.orglett.5b02900
|View full text |Cite
|
Sign up to set email alerts
|

β-C(sp3)–H Arylation of α-Hydroxy Acid Derivatives Utilizing Amino Acid as a Directing Group

Abstract: The Pd(II)-catalyzed intermolecular arylation of unactivated β-C(sp3)-H bonds in α-hydroxy acid derivatives was achieved. A variety of aryl iodides was tolerated giving moderate to good yields. The feasibility of amino acid auxiliary as a directing group was demonstrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Based on the above results, the Yu group explored the functionalization of O-protected α-hydroxy aliphatic acid derivatives by utilizing an amino acid DG (Scheme 88b). 262 A wide range of β-aryl-α-hydroxy acids were obtained in moderate to good yields without unwanted epimerization of the stereocenters.…”
Section: Palladium-catalyzed C(sp 3 )−H Functionalization Using Biden...mentioning
confidence: 93%
See 1 more Smart Citation
“…Based on the above results, the Yu group explored the functionalization of O-protected α-hydroxy aliphatic acid derivatives by utilizing an amino acid DG (Scheme 88b). 262 A wide range of β-aryl-α-hydroxy acids were obtained in moderate to good yields without unwanted epimerization of the stereocenters.…”
Section: Palladium-catalyzed C(sp 3 )−H Functionalization Using Biden...mentioning
confidence: 93%
“…Remarkably, selective arylation of tetrapeptides at the N-terminus has also been realized through minor modification of the reaction conditions. Based on the above results, the Yu group explored the functionalization of O -protected α-hydroxy aliphatic acid derivatives by utilizing an amino acid DG (Scheme b) . A wide range of β-aryl-α-hydroxy acids were obtained in moderate to good yields without unwanted epimerization of the stereocenters.…”
Section: Palladium-catalyzed Coordination-assisted C(sp3)–h Functiona...mentioning
confidence: 99%
“…However, the substrate scope was limited to aliphatic acids with a β-quaternary centre, due to the well-known Thorpe–Ingold effect in cyclopalladation17, and ratios of mono- to diarylated products in the range 2.5:1 to 5:1 were observed. Thus, the use of various directing groups to achieve regioselective β-C( sp 3 )–H bond functionalization of carboxylic acid derivatives18192021222324252627282930313233343536373839404142434445 has been extensively explored in the past decades (Fig. 1).…”
mentioning
confidence: 99%
“…38). In recent years, N , O -bidentate directing groups have been identified as being effective in directing site-selective C–H arylation of carboxylic acids in the presence of a palladium catalyst, and have been developed by the groups of Chatani39, Yu4041, Hong42 and Zhao43. Yu's group also demonstrated that mono-coordinated directing groups, such as perfluorinated aryl amides and N -methoxyamide, can effectively direct β-C( sp 3 )-H arylation with the assistance of mono- N -protected amino acid ligands (Fig.…”
mentioning
confidence: 99%
“…On the other hand, amino acids are excellent ligands for hard (higher‐valent) transition metal acceptors containing both N‐ and O‐donor functional groups as well as serving as transient directing groups for activation of inert C−H bonds . Amino acids are also known as common ligands for metal cations.…”
Section: Introductionmentioning
confidence: 99%